Integrated Management of Key Pests in Edamame Cultivation: Harnessing Biological Agents and Botanical Pesticides - Haryadi, Nanang Tri; Kurnianto, Agung Sih; Dewi, Nilasari; Natasyah, Defi Cindi; Oktaviani, Nabiila Salsabil; Saputro, Puguh Widianto; Putri, Rizka Adelia; Ruchma, Verdiana Wahyu Hidayati (AGRIVITA Journal of Agricultural Science, 2026)
Edamame (Glycine max L. Merr.) is a high-value crop and an export commodity  with  very  high  environmental  qualification  standards. Spodoptera litura and Bemisia tabaci reduce both the quantity and quality of production. Therefore, more environmentally friendly pest control methods are needed. This study evaluated several biological control agents. A field experiment was conducted using a Randomized Block Design with eleven treatments across three locations. The treatments included entomopathogenic fungi (Beauveria bassiana and Metarhizium anisopliae), Bacillus thuringiensis, Trichogramma sp., a botanical pesticide (1% azadirachtin), and light traps. All treatments were applied during the flowering stage. Spraying was carried out once a week, and parasitoids were released every two weeks. The results showed that pest populations changed over the observation period. The  population of B. tabaci decreased from week 4 to week 7, along with  increased  rainfall  and  enhanced  effectiveness  of  the  fungus. Treatments with combined biological agents with light traps produced highly consistent reductions in pest populations. This suggests that multiple integration of biological agents and physical traps provides stable pest suppression. Future optimization is more promising in terms of timing and long-term validation related to edamame management.